PENERAPAN STRATEGI BELAJAR SQ4R UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA POKOK BAHASAN STRUKTUR ATOM DI KELAS X MIA SMA MUHAMMADIYAH 1 PEKANBARU - Rinchian Fristi; Roza Linda; Johni Azmi (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Riau (UNRI), 2020)
The research on implementation of learning strategy to Survey, Question, Read, Recite, Record, Review (SQ4R) has been done to improve student achievement on the subject of Atomic Structures in class X MIA SMA Muhammadiyah 1 Pekanbaru on Agustus until September 2018. Form of the research is experimental research with pretest-posttest design. The sample consisted of two classes, class X MIA 2 as the experiment and class X MIA 3 as control class which randomly selected after had tested normality and homogeneity. Experimental class is a class that implemented Survey, Question, Read, Recite, Record, Review (SQ4R) strategy. Data analysis technique used the t-test. Based on the result of the final data processing t-test formula obtained tcount>ttable (1,86>1,67) means the application of Survey, Question, Read, Recite, Record, Review (SQ4R) strategy can improve student achievement on the subject of atomic structures in class X MIA SMA Muhammadiyah 1 Pekanbaru.